Perkawinan Tidak Tercatat (Kawin Siri) dalam Perspektif Hukum Negara dan Fatwa Islam di Indonesia dan Mesir - Mariatul Ulfah; Haidar Ali Mahmud Desky; M. Hasan Bisyri; Ali Trigiyatno (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
Unregistered marriage, commonly referred to as siri marriage, is a form of marital union conducted without official registration by state authorities. This phenomenon occurs quite frequently and has generated both juridical and theological debates in various countries, including Indonesia and Egypt. This study aims to compare the approaches of positive law and religious fatwas toward the practice of unregistered marriage in these two countries. In Indonesia, siri marriage is generally considered valid by the majority of Islamic scholars as long as it fulfills the pillars and conditions prescribed in Islamic law. Nevertheless, such marriages are generally discouraged because they are not registered at the Office of Religious Affairs (Kantor Urusan Agama/KUA), and therefore lack formal legal recognition under state law. As a consequence, the state is unable to guarantee or adequately protect the legal rights arising from the marriage. Religious fatwas in Indonesia typically affirm the sharīʿah validity of such marriages while simultaneously emphasizing the importance of official registration to ensure public welfare (maṣlaḥah) and legal protection for the parties involved. Meanwhile, in Egypt, unregistered marriage is likewise regarded as valid from the perspective of Islamic law. However, the Egyptian legal system requires official registration for a marriage to obtain formal legal recognition and to safeguard the civil rights of the spouses. Religious scholars in Egypt tend to adopt a stricter stance by emphasizing the urgency of registration in order to prevent misuse of the institution of marriage and to uphold social justice.